lnsan Kamil: Bentuk Teofani Paling Sempurna - Muzakki, Akhmad (ULUL ALBAB Jurnal Studi Islam, 2002)
The doctrine "wahdatul wudjud" developed by lbnu Arabi is considered a high tauhid. It states that the existence of things in the world is the reflection of Allah, the Oneness. Arabi further confirmes that human has a potential capability to manifest Allah s asma and aushaf. From this point, every human has great chance to realize the existence of the '"insan kamil" a reflection ofÂ Allah s tajalli, the special' position given to human as she/he perfectly reflects Allah s asma' and aushaf.